2020
DOI: 10.1002/jbmr.3978
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Reduction of Senescent Cell Burden Alleviates Focal Radiotherapy-Related Bone Loss

Abstract: Clinical radiotherapy treats life‐threatening cancers, but the radiation often affects neighboring normal tissues including bone. Acute effects of ionizing radiation include oxidative stress, DNA damage, and cellular apoptosis. We show in this study that a large proportion of bone marrow cells, osteoblasts, and matrix‐embedded osteocytes recover from these insults only to attain a senescent profile. Bone analyses of senescence‐associated genes, senescence‐associated beta‐galactosidase (SA‐β‐gal) activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 41 publications
8
119
0
Order By: Relevance
“…Dasatinib + Quercetin -Senescent HUVEC, senescent preadipocytes in vitro -Senescent MEFs, senescent bone marrow-derived murine mesenchymal stem cells in vivo -SA-β-gal positive muscle and fat tissue of irradiated single mouse limb -Progeroid Ercc1(−/∆) mice [186] -Senescent lung fibroblasts and epithelial cells in bleomycin-induced lung injury/idiopathic pulmonary fibrosis mouse model [18] -Senescent alveolar epithelial type (AT)II ex vivo in bleomycin-induced lung injury/idiopathic pulmonary fibrosis mouse model. [187] -Senescent medial aortal cells of aging mice and hypercholesterolemia (atherosclerosis) mouse models [188] -Senescent hepatocytes of dietary hepatic steatosis mouse model [189] -Radiation-induced senescent preadipocytes in vivo -Senescent cells in freshly isolated human omental adipose tissue of obese individuals ex vivo [190] -Arteriovenous fistula-chronic kidney disease mouse model [191] -20-month-old, transgenic tau NFT -Mapt 0/0 mice [192] -Aβ plaque-associated senescent oligodendrocyte progenitor cells in vivo -ZsGreen/APPPS1 p16 INK4 reporter Alzheimer's disease mouse model -Radiation-induced senescent N2a cells [193] -Uterine fibrosis mouse model [194] -Telomere dysfunction-induced senescent osteoblasts and osteocytes [195] Navitoclax (ABT263) -Radiation-induced, replication-exhausted and Ras-induced senescent WI38 fibroblasts in vitro -Radiation-induced senescent human IMR90 fibroblasts, human renal epithelial cells and mouse embryonic fibroblasts in vitro -Radiation-induced senescence in p16-3MR transgenic mouse model [196] -Radiation-induced senescent human umbilical vein epithelial cells, IMR90 human lung fibroblasts and mouse embryonic fibroblasts [197] -Radiation-induced senescent type II alveolar epithelial cells in vitro and in vivo [198] -Senescent pancreatic tissue of i4F mouse model [199] -Replicative-exhausted human mesenchymal stromal cells [200] -Aging-induced senescent cardiac myocytes -Myocardial infarction mouse model [201] -Senescent murine pancreatic β-cells in vitro and in vivo [202] -Aging mouse bone marrow stromal cells [203] -WIPI1 and SLITKR4 overexpression-induced senescent uterine leiomyoma spheroid model ex vivo [204]…”
Section: Senolytic Model/cell Line Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Dasatinib + Quercetin -Senescent HUVEC, senescent preadipocytes in vitro -Senescent MEFs, senescent bone marrow-derived murine mesenchymal stem cells in vivo -SA-β-gal positive muscle and fat tissue of irradiated single mouse limb -Progeroid Ercc1(−/∆) mice [186] -Senescent lung fibroblasts and epithelial cells in bleomycin-induced lung injury/idiopathic pulmonary fibrosis mouse model [18] -Senescent alveolar epithelial type (AT)II ex vivo in bleomycin-induced lung injury/idiopathic pulmonary fibrosis mouse model. [187] -Senescent medial aortal cells of aging mice and hypercholesterolemia (atherosclerosis) mouse models [188] -Senescent hepatocytes of dietary hepatic steatosis mouse model [189] -Radiation-induced senescent preadipocytes in vivo -Senescent cells in freshly isolated human omental adipose tissue of obese individuals ex vivo [190] -Arteriovenous fistula-chronic kidney disease mouse model [191] -20-month-old, transgenic tau NFT -Mapt 0/0 mice [192] -Aβ plaque-associated senescent oligodendrocyte progenitor cells in vivo -ZsGreen/APPPS1 p16 INK4 reporter Alzheimer's disease mouse model -Radiation-induced senescent N2a cells [193] -Uterine fibrosis mouse model [194] -Telomere dysfunction-induced senescent osteoblasts and osteocytes [195] Navitoclax (ABT263) -Radiation-induced, replication-exhausted and Ras-induced senescent WI38 fibroblasts in vitro -Radiation-induced senescent human IMR90 fibroblasts, human renal epithelial cells and mouse embryonic fibroblasts in vitro -Radiation-induced senescence in p16-3MR transgenic mouse model [196] -Radiation-induced senescent human umbilical vein epithelial cells, IMR90 human lung fibroblasts and mouse embryonic fibroblasts [197] -Radiation-induced senescent type II alveolar epithelial cells in vitro and in vivo [198] -Senescent pancreatic tissue of i4F mouse model [199] -Replicative-exhausted human mesenchymal stromal cells [200] -Aging-induced senescent cardiac myocytes -Myocardial infarction mouse model [201] -Senescent murine pancreatic β-cells in vitro and in vivo [202] -Aging mouse bone marrow stromal cells [203] -WIPI1 and SLITKR4 overexpression-induced senescent uterine leiomyoma spheroid model ex vivo [204]…”
Section: Senolytic Model/cell Line Referencementioning
confidence: 99%
“…Early results from the NCT02848131 clinical trial have demonstrated that the D+Q combination has successfully cleared senescent adipocytes in humans [224]. D+Q was shown to effectively clear senescent cells in several in vitro, in vivo and ex vivo in several disease models including Alzheimer's disease, obesity and radiation-induced tissue damage [190][191][192][193][194][195] (Table 2). Finally, it is important to mention that other preclinical evidence has suggested that D+Q might not be as effective in the clearance of senescent tumor cells as for aging-related pathologies [225].…”
Section: Dasatinib + Quercetinmentioning
confidence: 99%
“…Numerous strides have been made towards clearing senescent cells in order to restrain the detrimental effects of cellular senescence. Indeed, selective targeting of senescent cells using genetic models or senolytics has clearly demonstrated that inhibition of the SASP in both cancer, aging, and other models is beneficial (Bussian et al, 2018;Chandra et al, 2020;Chang et al, 2016;Demaria et al, 2017;Jeon et al, 2017;Justice et al, 2019;Perrott et al, 2017;Suvakov et al, 2019;Wiley et al, 2018;Xu et al, 2015). While inhibitors of NF-κβ suppress the SASP, they also reverse the senescence-associated cell cycle arrest (Chien et al, 2011a), which would not be desirable in the context of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports describing the role of cellular senescence in the pathophysiology of osteoporosis via altered expression of SASP factors 111,112 . Senescent cells accumulate in the bone microenvironment with aging and clearance of these cells using genetic and pharmaceutical interventions improves bone quality in aged mice 113,114 . In advanced aging, multiple cell types such as containing B cells, T cells, myeloid cells, osteoprogenitors, osteoblasts and osteocytes in the bone microenvironment become senescent, 115,116 although senescent myeloid cells and senescent osteocytes predominantly develop the SASP, a pro‐inflammatory environment 117 .…”
Section: Regulation Of Bone Homeostasismentioning
confidence: 99%